Contemporary TV Drama Series - Huber, Florian; Klaus, Elisabeth (Global Media Journal - German Edition, 2015)
Technological developments, especially the Internet, have changed the medium "television" profoundly. On the one hand, media convergence means watching television is no longer limited to a singular box with one screen. On the other hand, this is connected to profound changes in programming content. In addition to cheaper formats like daily talks and Reality-TV, complex and expensive television series, rather vaguely referred to as "Quality-TV", have conquered the TV market. They are sold internationally and aimed at an affluent, dedicated audience. The articles in this issue of the Global Media Journal deal with different aspects of what we refer to as "Contemporary Television Series", a less evaluative term. The transnational character of the shows is highlighted in two of the articles, while three authors focus on the perspective of the audience. The final two contributions grapple with the issue of quality as strategies of cultural legitimation and its aesthetic and ideological sides.